Dyskurs dydaktyczny w nauczaniu dwujęzycznym na przykładzie języka francuskiego - Sowa, Magdalena (Neofilolog, 2023)
The aim of the text is to describe the didactic discourse in bilingual education i.e. the actions taken by the teacher in biology and chemistry lessons in relation to the terms the student needs to know and assimilate. The description is based on transcriptions of audio recordings of lessons recorded in one of the bilingual high schools in Warsaw. Basing on selected excerpts from the collected corpus, the author i) shows examples of biology and chemistry terms having different forms in Polish and French and ii) defines the teacher's didactic activities, thanks to which the latter helps the students to properly understand and assimilate the elements of field terminology.